Pengaruh Media Pembelajaran Kahoot Terhadap Motivasi Dan Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas V SD Negeri 01 Fena Fafan - Hukunala, Desy; Ritiauw, Samuel P.; Ritiauw, Leonid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the difference between learning outcomes before and after using the Kahoot application in social studies lessons in Grade V elementary school. The research used a quantitative research design with a quasi-experimental approach and a non-equivalent control group design. The results showed that there was a significant increase in learning outcomes and motivation after using Kahoot media in Grade V students at Negeri 01 Fena Fafan Elementary School.